Microstructure evolution during hot deformation of as cast ESR-CDSed superalloy Rene88DT. (July 2014) - Li, F.; Fu, R.; Feng, D.; Tian, Z.
<x content-type="archive" xml:space="preserve">Abstract</x> The microstructure evolution during hot deformation of directionally solidified disc alloy Rene88DT produced by electroslag remelting continuous directionally solidification (ESR-CDS) was investigated by using optical microscope and electron backscatter diffraction technique. Hot compression tests were conducted at different strains at temperatures ranging from 1060 to 1140°C for strain rates between 0·001 and 1 s−1. Experimental results revealed that the process of dynamic recrystallisation (DRX) in as cast ESR-CDSed Rene88DT alloy can be classified into three periods, namely, incubation, nucleation and growth. Deformation temperature plays a significant role in recrystallisation grain nucleation and migration, which reveals that the size and fraction of DRX grain increases with the increasing temperature. Dynamic softening mechanisms vary depending on the hot deformation temperature. The microstructure evolutions during DRX are characterised in view of subgrain coarsening and strain induced grain boundary migration near the original columnar grain boundary.